Pengaruh Variasi Konsentrasi Larutan Naoh 6m Dan 8m Terhadap Penurunan Caco3 Pada Mortar Geopolimer Berbahan Dasar Fly Ash Nagan Raya - Aiyub Aiyub; Lia Ramadhaniati; Fajri Fajri (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
The combination of NaOH and Na2SiO3 in an alkaline solution is able to react with FA to form Si-O-Si and Si-O-Al gels. Several studies have shown that the high concentration of NaOH causes the appearance of calcium carbonate (CaCO3) on the surface of the specimen. This problem became the concern of this study, the reduction NaOH concentration was investigated to reduce CaCO3. The results showed that the chemical composition of FA Nagan Raya (FANR) contained Si, Al, and Ca compounds which were respectively around 37.16%, 17.61%, and 8.72%. XRD analysis shows that the main peaks of the FANR material and paste are in the 20 to 30 2θ region. FTIR analysis showed that the peak of the band 1380cm-1 - 1450cm-1, showed that the CaCO3 was bent in the FANR paste. The TGA analysis shows that the weight loss of FANR paste is higher than material of FANR. Low NaOH concentration has decreasing workability which causes faster setting time and reduces compressive strength. However, the use of a low concentration of NaOH solution can reduce CaCO3 on the surface of spesimen.